Possible waterways between the Marmara Sea and the Black Sea in the late Quaternary: evidence from ostracod and foraminifer assemblages in lakes Iznik and Sapanca, Turkey - Nazik, Atike; Meric, Engin; Avsar, Niyazi; Unlu, Selma; Esenli, Vildan; Gokasan, Erkan (SPRINGER, 2011)
In this study, the fossil microfaunal composition of 28 Recent sediment samples from Lake A degrees znik and 19 samples from Lake Sapanca was investigated. The presence of at least ten marine ostracod and 23 foraminifer species in the sediments of Lake A degrees znik, and at least one marine ostracod and two foraminifer species in the sediments of Lake Sapanca confirm that these lakes must have been connected to the world ocean sometime during the late Quaternary. The most obvious former link between these lakes and the Mediterranean Sea would have been via the Marmara Sea with an eastward extension of the Gemlik and A degrees zmit bays. The proximity of Lake Sapanca to the lower course of the Sakarya River, however, also supports earlier suggestions that there may have been a temporary connection with the Black Sea via this river valley. Whatever the case, the findings of this study clearly demonstrate that vertical tectonic movements need to be taken into account when reconstructing the late Quaternary sea-level history of this region.
Keywords: NORTH ANATOLIAN FAULT; NW TURKEY; MEDITERRANEAN SEA; EVOLUTION; OUTFLOW; SHELF; REGION; LEVEL; SOUTH; GULF; Geology; Oceanography